CD22 Is Required for Protection against West Nile Virus Infection - Ma, Daphne Y. (American Society for Microbiology, 2013)
West Nile virus (WNV) is a RNA virus of the family Flaviviridae and the leading cause of mosquito-borne encephalitis in the United States. Humoral immunity is essential for protection against WNV infection; however, the requirements for initiating effective antibody responses against WNV infection are still unclear. CD22 (Siglec-2) is expressed on B cells and regulates B cell receptor signaling, cell survival, proliferation, and antibody production. In this study, we investigated how CD22 contributes to protection against WNV infection and found that CD22 knockout (Cd22(−/−)) mice were highly susceptible to WNV infection and had increased viral loads in the serum and central nervous system (CNS) compared to wild-type (WT) mice. This was not due to a defect in humoral immunity, as Cd22(−/−) mice had normal WNV-specific antibody responses. However, Cd22(−/−) mice had decreased WNV-specific CD8(+) T cell responses compared to those of WT mice. These defects were not simply due to reduced cytotoxic activity or increased cell death but, rather, were associated with decreased lymphocyte migration into the draining lymph nodes (dLNs) of infected Cd22(−/−) mice. Cd22(−/−) mice had reduced production of the chemokine CCL3 in the dLNs after infection, suggesting that CD22 affects chemotaxis via controlling chemokine production. CD22 was not restricted to B cells but was also expressed on a subset of splenic DCIR2(+) dendritic cells that rapidly expand early after WNV infection. Thus, CD22 plays an essential role in controlling WNV infection by governing cell migration and CD8(+) T cell responses.